Developing a model for studying complex brain function using zebrafish (Danio rerio) and cavefish (Astyanax mexicanus) - Ahmad Zaki, Nabila Irqin (2015)
The zebrafish (Danio rerio) has been used as a model organism for studies in developmental biology. In fact, several common and important developmental genes mechanisms have been identified in zebrafish, which are similar in mammals. There is also growing research in the cognitive and memory functions in the laboratory animals over last decade, however the interests in the behavioral features of zebrafish are limited. In contrast to zebrafish, the cognitive function for cavefish (Astyanax mexicanus) is based on mechanosensory systems and their lateral line, which is highly sensitive to fluctuating water movement and pressure. Many evolution researches have been done to these cavefish reported that they have better olfactory sense by having taste buds all over its head which help them find food more quickly in complete darkness. In addition, the mechanosensory lateral line system helps them to perceive their environment. While rodents have traditionally been used to study cognitive and memory functions, the zebrafish are gaining popularity as an excellent vertebrate model to complement current translational neuroscience research. Thus, the study purpose in this application is to compare the learning and memory functions of both character of fish, zebrafish and cavefish using the Y-maze task. Results showed that there is no significant differences on cavefish enter and spent time in the Y-maze arms. However, time spent and numbers of entries in the novel arm were significantly higher in the zebrafish. Thus, the cognitive function of cavefish is based on their characteristics and the zebrafish is based on the visual queue of the Y-maze task.